ANALISIS DAYA TARIK WISATA MINAT KHUSUS DI BALIWOSO CAMP DESA PENGOTAN KABUPATEN BANGLI - Purba, Ade Wani Br; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p29, 2016)
Baliwoso camp that is located in Pengotan Village, Bangli Regency. Pengotan village has relatively cool temperature, with orange and coffee as the main commodity in this village. Baliwoso Camp presence drives the tourism in Pengotan Village, especially for special interest tourists who want to feel different sensations in his leisure. With the potiential of its tourism of Baliwoso Camp, which is closely related to the world of the campsite and to introduce local culture. Baliwoso Camp packages it in a modern way so that there is interest alone to research more deeply about the potential for special interest tourism in Baliwoso Camp. This research will be discussed to identify the components of tourism in Baliwoso Camp with 4A concept that focuses on attraction an activity, accessibility, amenity and ancilliary. To know the potential is done by direct observation and interviews with owner of Baliwoso Camp in Pengotan Village. With four categories of potential tourist attraction special interest in Baliwoso Camp knowable. Tourism potiential in Baliwoso Camp is natural and artificial is characteristic. With champsite atmosphere more attractive for special interest tourist. Local people who are active in Pengotan Village become one of the potential that can be developed in Baliwoso Camp. The category may also indicate the extent to which the development Baliwoso Camp both physical and non physical. It affects the local communities so that they can build a better future of Pengotan Village.
Keywords: ourism potential, atraction, accessibility, amenity, and ancilliary.